First record of bats (Mammalia: Chiroptera) from mangrove in Dam Nai area, Ninh Thuan province, central Vietnam - Thong, Vu Dinh (Academia Journal of Biology, 2021)
Dam Nai is one of the twelve best known lagoons in south central Vietnam. Habitats in and around the largoon and its surroundings are quite diverse including mangrove, bushes, rice fields and fruit tree farms which are ecologically suitable for many animals including bats. However, bats in this area still receives very little attention from scientists. The author conducted a series of bat surveys since 2017 for the primary understanding of bats inhabiting this area before the establishment of a wind farm. The results show the records of two nationally rare fruit bat species, Cynopterus brachyotis and Macroglossus minimus, from mangrove in this area. Morphological features and detailed records of these two species are given in this paper with recommendations for further researches for conservation.